h+(4t*4t)-8t=48

Simple and best practice solution for h+(4t*4t)-8t=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h+(4t*4t)-8t=48 equation:


Simplifying
h + (4t * 4t) + -8t = 48

Reorder the terms for easier multiplication:
h + (4 * 4t * t) + -8t = 48

Multiply 4 * 4
h + (16t * t) + -8t = 48

Multiply t * t
h + (16t2) + -8t = 48

Reorder the terms:
h + -8t + (16t2) = 48

Solving
h + -8t + (16t2) = 48

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '8t' to each side of the equation.
h + -8t + 8t + (16t2) = 48 + 8t

Combine like terms: -8t + 8t = 0
h + 0 + (16t2) = 48 + 8t
h + (16t2) = 48 + 8t

Add '(-16t2)' to each side of the equation.
h + (16t2) + (-16t2) = 48 + 8t + (-16t2)

Combine like terms: (16t2) + (-16t2) = 0
h + 0 = 48 + 8t + (-16t2)
h = 48 + 8t + (-16t2)

Simplifying
h = 48 + 8t + (-16t2)

See similar equations:

| 1.4+0.5c-c=0.6c+0.3 | | 1.25x-.75=.83333x+.5 | | 2c^2-15c+28=0 | | 2x^4-x^3+16x-8=0 | | 8+2/5(3x-1)=-2+1/2(20-3x) | | 1.25x-.75=.833x+.5 | | 0.5(x-3)+(1.5-x)=5x | | 9z-(6-z)=12z-10 | | -x+9=20-3x | | 5x+6x-20=5x-8 | | 3x-10=75-2x | | 9Y^2=36Y-35 | | (5x+7)(3x-8)=(5x+4)(3x-5) | | 4-4x=19-9x | | 3x=y-4 | | 190-x=215 | | 100=-0.001x^2+0.3x | | 150=-0.002x^2+0.3x | | .75x+19=-11 | | 9x-21=3x+33 | | .6(z-300)+.05z=.7z-205 | | 3/2(8x+10)-3/5(10x-5)=0 | | y^2-14y-13=0 | | 777=-16t^2+52t+16 | | 2x=4-7y | | (5x+7)(3x-8)=(5x+4)(3x+5) | | 5-2(x-2)=3(x+4) | | 400=-16t^2+45t+5 | | 39=-16t^2+45t+5 | | 5s+4t+12s+t= | | 5x-3x^2+16= | | 4/3(12x+36)=1/2(96+32x) |

Equations solver categories